Identifikasi Spesies Ikan Kerapu di Pasar Ikan Karangasem dan Kedonganan Bali Menggunakan DNA Mitokondria Gen 16s rRNA IDENTIFICATION OF GROUPER SPECIES USING 16S rRNA MITOCHONDRIAL DNA IN KARANGASEM AND KEDONGANAN FISH MARKET, BALI - Sari Hadiprata, Ni Luh Made Ika Yulita; Putra, I Made Bagus Arya Permana Ardiana; Mahardika, I Gusti Ngurah Kade; Wandia, I Nengah; Nindhia, Tjokorda Sari (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
Groupers are bio-indicators of the health of coral ecosystems and high economic value. Various speciesof grouper fish sold in markets in Indonesia is not known. The purpose of this study was to identify thespecies of grouper fish market located in Karangasem and Kedonganan. The method used in this studywas polymerase chain reaction(PCR) techniqueand mitochondrial DNA 16S rRNA gene as a molecularmarker. Grouper samples were collected from the fish market Karangasem total of 11 samples and 42samples collected from Kedonganan. Sequences from each sample was obtained from the analysis inBerkeley Sequencing Facility, California. Sequencing samples were then analyzed by BLAST and matchedwith the sequences found in GenBank. The analysis showed that six species can be identified from the fishmarket Karangasem namely Cephalopholis leopardus, C.cyanostigma, C. miniata, C. sonnerati, Variolaalbimarginata, and Epinephelus fasciatus. Seven species can be identified in the fish market Kedonganannamely E. fuscoguttatus, E. coeruleopunctatus, E. merra, E. polyphekadion, C. cyanostigma, C. miniata andV.albimarginata.
Keywords: grouper fish, 16S rRNA mitochondrial DNA, Karangasem, Kedonganan